2020
DOI: 10.1002/etc.4844
|View full text |Cite
|
Sign up to set email alerts
|

Simulating Honey Bee Large‐Scale Colony Feeding Studies Using the BEEHAVE Model—Part II: Analysis of Overwintering Outcomes

Abstract: Large-scale colony feeding studies (LSCFSs) aim to assess potential pesticide exposure to and effects on honey bees at the colony level. However, these studies are sometimes affected by high losses of control colonies, indicating that other stressors may impact colonies and confound the analysis of potential pesticide impacts. We assessed the study design and environmental conditions experienced by the untreated control colonies across 7 LSCFSs conducted in North Carolina (USA). Overwintering success differed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…These 2 endpoints were identified as most indicative of colony health (e.g., Genersch et al 2010; Austin 2014; Döke et al 2015) and had the lowest uncertainty in data reported from the studies. Fall was identified as a particularly important time of the year because colony condition prior to overwintering is related to subsequent overwinter survival (Abi‐Akar et al 2020, this issue). The parameter combination that resulted in the best match between apiary‐specific simulations and CCA data with the uncertainty range applied is summarized in Table 3.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These 2 endpoints were identified as most indicative of colony health (e.g., Genersch et al 2010; Austin 2014; Döke et al 2015) and had the lowest uncertainty in data reported from the studies. Fall was identified as a particularly important time of the year because colony condition prior to overwintering is related to subsequent overwinter survival (Abi‐Akar et al 2020, this issue). The parameter combination that resulted in the best match between apiary‐specific simulations and CCA data with the uncertainty range applied is summarized in Table 3.…”
Section: Resultsmentioning
confidence: 99%
“…The remaining variabilities between colonies experiencing very similar conditions and management point to factors influencing colony dynamics that are beyond what can be reasonably controlled in a field‐based study. Large variability in outcomes of overwintering success (Abi‐Akar et al 2020, this issue) further suggests that factors may be influencing colony dynamics and overwintering success in LSCFSs that are currently not well understood. Such factors and processes are not captured in BEEHAVE because the model is based on current knowledge about honey bee colonies, and on initial conditions and other factors reported in the studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the process of full model creation is long and complicated and the most developed model nowadays, BEEHAVE (Becher et al 2014), is available on the project's website and can be freely downloaded and used (BEEHAVE -The Model 2013), the author decided to expand it and create dedicated modules describing "G-forced" specimens. Predictions correctness of the BEEHAVE has been confirmed multiple times by different scientific groups (Horn et al 2016, Agatz et al 2019, Abi-Akar et al 2020). The model is based on the NetLogo software, making it simple to use while keeping high development possibilities (Tisue and Wilensky 2004).…”
Section: Future Work -Computer Model Implementationmentioning
confidence: 71%
“…The original BEEHAVE model (Becher et al., 2013, 2014) was used to simulate the impacts of foraging stress (Horn et al., 2015), pesticides and pharmaceuticals (Rumkee et al., 2015; Carter et al., 2020), the Asian hornet, Vespa velutina (Requier et al., 2020), sublethal effects (Thorbek et al., 2017a, Schmolke et al., 2019) and to evaluate overwintering success (Abi‐Akar et al., 2020) and pesticide protection goals (Thorbek et al., 2017b). There has been development of BEEHAVE relating to foraging (BEESCOUT; Becher et al., 2016), a pollen exposure‐effects module (explicitly linking exposure to pesticide residues in pollen with colony effects, Schmolke et al., 2019) and model evaluation using field data (Agatz et al., 2019; Schmolke et al., 2020), which addresses some of the issues raised previously (EFSA PPR Panel, 2015).…”
Section: A Systems‐based Approach Of Multiple Stressors In Honey Bee Coloniesmentioning
confidence: 99%